Breaking Glass: A Pedagogical Approach to Understanding Voice in Media - (:unkn) unknown (My University, 2023)
This dissertation aims to examine the remediation of voices in media, specifically focusing on the reproduction of voices across different genres and the pedagogical approaches used to teach writing and media literacy. Much of the extant media is created with practices that historically have excluded minority groups, such as people with disabilities and people who speak other languages in addition to English in the US. This project develops a theory of interstices, which are both physical and metaphorical spaces in genres that can become sites of intervention through the composition process. These interstices are burdened by their many complex relationships between other formal elements of the genre and medium as well as by the social contexts surrounding the text’s production. To account for and name these relations, this project applies Thing Theory to understand the formal functions of the genres and will highlight unconventional examples of generic conventions of reproducing the voice. This project demonstrates examples of media that promote access and inclusivity by how they reproduce the voice and provide examples for instructors to use in higher-education classrooms, with the intention of addressing issues of inaccessible space in media.